The Hodge Theory Of Projective Manifolds. - De Cataldo, Mark Andrea (World Scientific, 2007)
This book is a written-up and expanded version of eight lectures on the Hodge theory of projective manifolds. It assumes very little background and aims at describing how the theory becomes progressively richer and more beautiful as one specializes from Riemannian, to Khler, to complex projective manifolds. Though the proof of the Hodge Theorem is omitted, its consequences topological, geometrical and algebraic are discussed at some length. The special properties of complex projective manifolds constitute an important body of knowledge and readers are guided through it with the help of se.